Effects of oxiris® therapy on cytokine elimination after a LPS infusion: an experimental animal study - Kalenka, Armin; Arens, Philipp; Müllenbach, Ralf M.; Weigand, Markus A.; Brune, Maik; Fiedler-Kalenka, Mascha (International journal of molecular sciences, 2024)
The clinical effectiveness of Oxiris®, particularly in reducing cytokines, remains uncertain due to the limited data provided. This study explored and analyzed the application value of Oxiris® endotoxin adsorption technology in a large animal model. Pigs received an intravenous LPS infusion. Six animals were treated 2 h after the infusion with an Oxiris® hemadsorption using a pumpless extracorporeal technique for 6 h. Five animals served as controls. Cardiocirculatory parameters, hyperspectral analysis, and a panel of cytokines were measured. The lipopolysaccharide infusion induced sepsis-like inflammation with tachycardia, elevated pulmonary pressure, elevated lactate level, as well as elevated pro-inflammatory cytokines like interferon (IFN)-γ, interleukin (IL)-1β, IL-2, IL-6, IL-8, IL-12 and tumor necrosis factor alpha (TNF-α). In addition, increases of anti-inflammatory cytokines like IL-1ra and IL-10 were found. After 3 and 6 h in both groups, pro-inflammatory cytokines were significantly reduced. No differences between the intervention and the control group could be detected after 3 and 6 h for IL-1β, IL-2, IL-6, IL-8, IL-12 and TNF-α, suggesting no effect of the Oxiris® filter on the elimination of elevated cytokines with a pumpless extracorporeal hemadsorption technique. The presented large animal model may be a promising option for studying the effects of hemadsorption techniques.
Im Text ist "®" hochgestellt
Gesehen am 10.02.2025